From Theory to Action: Developing Student Creativity through Project Learning in Chemistry - Rosmaria (EduTech Journal, 2025)
This study aims to analyze the development of student creativity through the implementation of project-based learning (PBL) in chemistry subjects. Using qualitative methods, data were obtained from interviews, observations, and document analysis related to projects carried out in class. The results showed that PBL improved students' understanding of chemical concepts and triggered students' creativity in designing experiments and solving problems. Students felt more involved and were able to relate chemical theory to practical applications in everyday life. The findings also showed increased student motivation and a more interactive classroom atmosphere. This study emphasizes the importance of integrating a practical approach in science education to form an innovative generation. By implementing PBL, students not only learn theory but also develop critical thinking skills needed to face future challenges.